Strategi Pengajaran Fikih pada Siswa Madrasah Ibtidaiyah di MI Datarbungur - Lina Lisnawati (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
This study aims to reveal and describe the learning strategy of Fiqh subjects in Datarbungur Elementary Madrasah. The main focus of the study covers three important aspects, namely the scope of Fiqh subject matter, the learning implementation process, and the achievement of student learning outcomes. The approach used is descriptive qualitative, with data collection techniques in the form of observation, interviews, and documentation, as well as data presentation supplemented with critical analysis. The results of the study indicate that the Fiqh learning strategy in Datarbungur Elementary Madrasah has been implemented well and efficiently. This is shown through several main indicators: first, Fiqh material covers the affective, cognitive, and psychomotor domains in a balanced and integrated manner; second, the learning process applies a constructivist approach that is able to increase active student participation and encourage deep understanding; third, student learning outcomes are classified as good because learning is carried out contextually and based on problem solving, relevant to students' experiences and daily lives.